Influence Of Development Index Components Humans On Economic Growth In Bali 2012-2019 - Ni Komang Octavia GIRI; Putu Ngurah Suyatna YASA; A.A Ketut JAYAWARSA (Indonesia Strategic Sustainability, 2022)
Human development is one indicator of achieving economic development. Granting human development increases every year, inequality in human development is motionless discernable between districts/cities in the province of Bali. Furthermore, this study aims to determine the effect of life expectancy, literacy rate, average school length and real expenditure per capita on economic growth. The data used was secondary data downloaded from the Central Agency in Statistics of Bali Province and was a 2012 - 2019 time series. The descriptive qualitative method applied to analyze the data in this study. The results of data processing were composed of life expectancy has a positive effect on economic growth, literacy rates have a negative effect on economic growth, the average school length has a positive and insignificant effect on economic growth, and real expenditure per capita has a significant negative effect on economic growth of Districts / City in Bali. Formerly, The Government is expected to increase further performance that is capable of improving the quality of education in the Districts / City in Bali. Education level must be considered thoughtfully to promote better economic growth and per capita expenditure needs to be stabilized every year.